Indolylvinyl Ketones: Building Blocks for the Synthesis of Natural Products and Bioactive Compounds - Trushkov, Igor V.; Uchuskin, Maxim G.; Abaev, Vladimir T.; Serdyuk, Olga V. (Synthesis, 2019)
Indolylvinyl ketones are valuable building blocks that can be utilized for the synthesis of numerous natural products and bioactive molecules containing an indole core motif. Herein, we describe their application for the total synthesis of some alkaloids, their analogues, and a variety of other important compounds, with an emphasis on biologically active examples.1 Introduction2 Functionalization of the Enone C=C Bond2.1 Reduction2.2 Michael Addition2.3 Cycloaddition3 Transformation of the Carbonyl Group3.1 Reduction3.2 Knoevenagel Reaction3.3 Addition of Organometallic Compounds3.4 Olefination4 Reactions Involving the Enone Conjugate System С=С–С=О4.1 Reactions with 1,2-Dinucleophiles4.2 Reactions with Compounds Bearing an Active Methylene Group4.3 Reactions with 1,3-Dinucleophiles4.4 Reactions with 1,4-Dinucleophiles5 Functionalization of the Enone Methylene Group C(O)–CH2R5.1 Acylation/Crotonic Condensation and Related Transformations5.2 Enolization6 Functionalization of the Indole Core6.1 [4+2] Cycloaddition6.2 [3+3] Annulation6.3 Electrocyclic Reactions7 Miscellaneous8 Conclusions
Keywords: indoles; ketones; total synthesis; natural products; alkaloids; bioactive compounds